The Effect of Liquidity and Profitability on Stock Prices in Agricultural Sector Companies Listed on the Indonesia Stock Exchange - Maria Sriratna Jawa; Alosius Hama (Journal of Creative Power and Ambition (JCPA), 2026)
This study was designed to evaluate the relationship between the level of liquidity, which is measured through the Current Ratio (CR), and that represented by Return on Assets (ROA), which is represented by Return on Assets (ROA), a measure of stock price dynamics in agricultural sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Using a quantitative methodology with a descriptive narcissist, this study engages a business entity as a sample that is a sample through purposive sampling techniques. The analysis of the kuranda data used multiple regression lines to test the hypothesis partially simultaneously. The research findings indicate that independently, the CR variable is not made of a meaningful influence that means the value of the stock, while ROA has a positive and significant impact. However, testing collectively proves that liquidity and profitability together affect the movement of stock prices. This result is a signal to investors that the efficiency management set in profit products is the main indicator in the investment efficiency in the financial sector.